(3QSGdI aj CaVdjI eMeO Ydjg GdSdGe Ydi SGFQ GdCfHjGA hGdQSd Ydjge GdSdGes - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi cQe Hfi BOe haVdfG Ydi SGFQ GdGee hHYO agPg QSGdI eYehdI ai JMbjb Jdc GdebGdI afbhd hef Gddg GdJhajb Chd GdCfHjGA BOe hBNQge jYO eMeO s
(3BNQgG (B:s
(3Cf GdcaQ ai GdCHGA fbU ai TQa GdfSH hdjS gfG VQhQI OYJg Edi GdJUQjM HeG PcQg Ydi Efg eNJda ajg Hjf GdSda hdG Odjd bGWY dCMO GdaQjbjf Je s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI (B15s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9237) s
Keywords: (3GdJhMjO hGdedd hGdfMds